Hydration and dissociation of hydrogen fluoric acid (HF) - Odde, Srinivas; Mhin, Byung Jin; Lee, Kyu Hwan; Lee, Han Myoung; Tarakeshwar, P.; Kim, Kwang. S. (AMER CHEMICAL SOC, 2006)
The hydration and dissociation phenomena of HF(H2O)(n) (n <= 10) clusters have been studied by using both the density functional theory with the 6-311++G**[sp] basis set and the Moller-Plesset second-order perturbation theory with the aug-cc-pVDZ+(2s2p/2s) basis set. The structures for n g 8 are first reported here. The dissociated form of the hydrogen-fluoric acid in HF( H2O) n clusters is found to be less stable at 0 K than the undissociated form until n = 10. HF may not be dissociated at 0 K solely by water molecules because the HF H bond is stronger than the OH H bond, against the expectation that the dissociated HF(H2O) n would be more stable than the undissociated one in the presence of a number of water molecules. The dissociation would be possible for only a fraction of a number of hydrated HF clusters by the Boltzmann distribution at finite temperatures. This is in sharp contrast to other hydrogen halide acids (HCl, HBr, HI) showing the dissociation phenomena at 0 K for n >= 4. The IR spectra of dissociated and undissociated structures of HF(H2O) n are compared. The structures and binding energies of HF( H2O) n are found to be similar to those of (H2O)(n+1). It is interesting that HF(H2O)(n=5,6,10) are slightly less stable compared with other sizes of clusters, just like the fact that (H2O)(n=6,7,11) are slightly less stable. The present study would be useful for the experimental/ spectroscopic investigation of not only the dissociation phenomena of HF but also the similarity of the HF-water clusters to the water clusters.
Keywords: MOLECULAR-DYNAMICS SIMULATIONS; PROTONATED WATER CLUSTERS; AB-INITIO; EXCESS ELECTRON; VIBRATIONAL-SPECTRA; SULFURIC-ACID; GAS-PHASE; ENERGETICS; HCL; (H2O)(N)